2017
DOI: 10.12816/0038664
|View full text |Cite
|
Sign up to set email alerts
|

Photographic Analysis of Macro- and Micro-Aesthetic Appearance in a Sample of Iraqi Adults with Class I Normal Occlusion

Abstract: Background: Generally, the facial esthetics depends on the esthetic appearance of the maxillary anterior teeth. The purposes of this study were to analyse the macro-aesthetic appearance of the face and the micro-aesthetic appearance of the maxillary anterior teeth to establish the normative values for class I normal occlusion and to detect possible gender differences. Materials and methods: The sample consisted of 120 Iraqi adults (60 males and 60 females) aged (18-23) years. Each individual was clinically exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
2
0
0
Order By: Relevance
“…With ULV mean value of 5.83 mm for males group and 6.82 mm for females group and LLV mean value of 9.17 mm for males group and 10.14 mm for females group. It seems that the Egyptian upper lip vermilion ULV and lower lip vermilion LLV values were closer to those of the Iraqi population, Mohammed et al (24) found in Iraqi individuals with the same age group as in the present study mean values of 5.33 mm for ULV and 10.11 mm for LLV for the male group and 5.38 mm for ULV and 10.29 mm for LLV for the female group. While Sawyer et al (25) found that in young Caucasian subjects, all lip parameters were larger in males group than in females group, this could be attributed to ethnical differences.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…With ULV mean value of 5.83 mm for males group and 6.82 mm for females group and LLV mean value of 9.17 mm for males group and 10.14 mm for females group. It seems that the Egyptian upper lip vermilion ULV and lower lip vermilion LLV values were closer to those of the Iraqi population, Mohammed et al (24) found in Iraqi individuals with the same age group as in the present study mean values of 5.33 mm for ULV and 10.11 mm for LLV for the male group and 5.38 mm for ULV and 10.29 mm for LLV for the female group. While Sawyer et al (25) found that in young Caucasian subjects, all lip parameters were larger in males group than in females group, this could be attributed to ethnical differences.…”
Section: Discussionsupporting
confidence: 80%
“…These findings were in agreement with Bishara et al (15) who found that in Egyptian individuals the mean values of the maxillary anterior teeth parameters were higher in males group than in females group and with Farag et al (30) who found that females had significantly smaller maxillary anterior teeth than males. In other populations with same age group of the present study, Mohammed et al (24) found that in Iraqi individuals the mean values of the maxillary anterior teeth parameters were higher in males group than in females group except for the mesiodistal width of left and right lateral incisor. While, Subhashini et al (31) found that in South Indian population the mesiodistal widths of the maxillary anterior dentition were larger in males group than females group including the lateral incisors mesiodestal width.…”
Section: Discussionsupporting
confidence: 66%
“…As per studies despite the prevalence of different ethnic populations all around the world, everyone gets attracted by a beautiful face. Beauty of the face is comprised of a balance of features, symmetry, harmony, and complexion 11 . However, there are faces that are asymmetrical and yet are considered as beautiful.…”
Section: Discussionmentioning
confidence: 99%